Scientometric Knowledge Mapping of 3D Concrete Printing Research and Perceptions from South Africa: Trends and Sustainable Prospects - Jacob Adedeji Adedeji; Nura Shehu Aliyu Yaro; Adeyinka Kabir Akanbi; Xoliswa Evelyn Feikie; Mohamed Mostafa Hassan Mostafa (Disaster in Civil Engineering and Architecture, 2026)
This research focuses on scientometric knowledge mapping and trend analysis of three-dimensional concrete printing (3DCP). It is a study based on South African perspectives, and the extracted bibliographic data are from the Scopus and Web of Science databases for the periods of 2015 and 2025. Fifty (50) articles were analysed using performance indicators and science mapping methods to investigate publication trends, key sources, affiliations, funding agencies, and research themes related to 3D concrete printing construction materials. The results reveal a marked increase in publication output related to digital construction and additive manufacturing technologies, particularly from 2020 onwards, reflecting increased scholarly attention at both the national and global levels. There is a strong alignment with sustainable development goals 9, 11, and 12 with the bibliographic data through keyword co-occurrence, revealing varying research emphasis. Approximately 10% of the studies focused on printable concrete sustainability, 20% on rheology, 30% on numerical modelling, 40% on sustainability, 50% on performance, 60% on interlayer bond strength, and up to 70–80% on material innovations, including supplementary cementitious material and alternative binders. The research output of South Africa is driven primarily by research-intensive universities and national science institutions, such as Stellenbosch University, the University of Johannesburg, the University of the Witwatersrand, and the Council for Scientific and Industrial Research. These efforts are supported by funding from the Department of Science and Innovation, National Research Foundation, South African Research Chairs Initiative, and European Commission-funded collaborations. These findings provide evidence to inform future research and policy on sustainable digitally enabled construction materials; however, significant knowledge gaps still remain in areas such as durability, standardization, and large-scale implementation.